Capital statement analysis as a tool to detect tax evasion. Issue 5 (10th September 2018) - Nawawi, Anuar; Salin, Ahmad Saiful Azlin Puteh
Abstract : Purpose: The purpose of this study is to determine the suitability of capital statement analysis in assisting tax investigation to combat tax evasion, measured by the time taken in proving the under-declared income by the tax evader. A weakness in the investigation process that may contribute toward the delay of the tax investigation completion was examined. Design/methodology/approach: Five investigation cases were randomly selected from the tax investigation organization for detailed and in-depth analysis on the whole process of reconstruction of capital statement analysis. Document analysis technique was used to analyse the data. Findings: This study found that the capital statement analysis can be an effective tool in detecting under-reported income and tax evasion. However, the cooperation from the taxpayer is the most important factor, because if taxpayers do not cooperate, the investigation officer needs to find other informant such as third party as a source of information which usually time-consuming. Research limitations/implications: This paper selected only a small number of tax fraud cases for examination. Many other cases were not accessible due to confidentiality and considered as high-profile cases. Practical implications: The outcome of this paper contributes in the way it can be used and applied by the revenue authority in implementing more practical and effective capital statement analysis technique to deter tax evasion. The investigation activities can be improved so that more cases can be covered in shorter time period. Originality/value: The paper is novel and original, as it focuses on the investigation of tax fraud cases' which is difficult to access and rare in tax literature, particularly in emerging markets. The findings of this study are inferred from direct examination of the actual cases documents that are private and confidential.